Psychiatry in the Soviet Union - Wing, J. K. (1974)
The services for chronically handicapped people with psychiatric disorders in the Soviet Union are described. The system is based upon a network of community units, each of which includes a day centre, a follow-up clinic, and a sheltered workshop. British services could profitably learn from the experience of these units. The diagnostic system used by many Soviet psychiatrists is different from that incorporated in the International Classification of Diseases. In particular, the term “schizophrenia” is used to describe conditions which British psychiatrists would label in other ways. This clinical difference partly explains the different concept of “criminal responsibility,” but another large component of the difference is political rather than medical. There are also variations from British practice in certain juridical procedures. These differences together make Soviet psychiatric practice in the case of political dissenters unacceptable to most British psychiatrists. It is too soon to say that frank discussions of these matters could not lead to improvement. British and Soviet psychiatrists still have something to learn from each other.